The Securitization of Ebola in Canadian Media Discourses - Durocher, Laurence (Université d'Ottawa | University of Ottawa, 2018)
In 2015, the international community was struggling to put an end to the largest and most violent Ebola outbreak of its 40-year-old history (CDC, 2015). This outbreak attracted unprecedented attention from both public health specialists and worldwide media consortiums. The scale of this human disaster raises important questions about our vulnerabilities and our level of preparedness towards infectious agents, but also on our perception of risks in this increasing global culture of security. This research aims to explore the processes of securitization of the 2014-2015 West African Ebola outbreak in Canadian media. Building from the Copenhagen School’s theory of securitization, we conducted a discourse analysis of the news stories published about the latest Ebola epidemic in two mainstream Canadian newspapers (Globe and Mail and La Presse) over a year-long period. The results of this analysis have shown that the securitization of Ebola in Canadian media mostly took place through the deployment of a grammar of security as well as the use of the two complex set of narratives related to globalization and local politics. This study has implications for our understanding of the securitization theory as well as global health governance mechanisms and emergency responses linked to communicable diseases like Ebola. More broadly, this analysis intends to start the reflection on whether positioning an outbreak following a rhetoric of security happens to be the most adequate option to guide Canadian interventions in times of public health crises. Key words: Security, Securitization, Ebola, Media, Health, Epidemics, Discourse Analysis